Draft environmental statement : proposed 1977 outer continental shelf oil and gas lease sale, offshore the North-Atlantic States, OCS sale no. 42 - United States. Bureau of Land Management. ([Washington, D.C.] : The Bureau : U.S. Govt. Print. Off., 1976)
At head of title: United States Department of the Interior. Bibliography: v. 3, p. 1334-1380. Mode of access: Internet.